PERANAN MANAJEMEN LABA DALAM MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI - Sylvia; Prastowo D, Dwi; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2020)
The objective of this research is to examine and analyze which factors will affect bond rating with earnings management as variable moderating for listed companies from 2014-2018. The factors in this research are growth which represented by asset and sales growth, corporate governance which represented by audit committee and financial performance which represented by profitability. The moderating variable is earnings management. Population of this research is companies that are listed in Indonesia Stock Exchange. This research use a purposive sampling method to determine research samples with specific criteria, whereas the method of analysis is going to use SEM-PLS. The source of data for this research is obtained from Bond Book Report, Financial Report, and Annual Report. This research found that growth has no effect on bond rating, audit committee has no effect on bond rating while profitability has an effect on bond rating. Audit committee and profitability which moderated by earnings management has no effect on bond ratings, while growth which moderated by earnings management has an effect on bond ratings.